PENYULUHAN PENGELOLAAN LIMBAH CAIR TEMPE-TAHU USAHA KECIL MENENGAH (UKM) SEMANAN, KECAMATAN KALIDERES, KOTA JAKARTA BARAT - Tazkiaturrizki; Sarah Aphirta; Wisely Yahya; Feri Wardianto; Ariani Dwi Astuti; Widyo Astono (ADPERTISI, 2024)
In Indonesia, particularly in Semanan, tofu, and tempe are produced by home industries using traditional technology. However, the soybean processing industry is considered inefficient. The process used is considered not environmentally friendly. This Community Service activity aims to provide insight to the target audience regarding the integrated management of tofu-tempe wastewater. There are 3 stages in this activity. The first stage (1) is preparation. The second stage (2) is implementation. The third stage (3) is evaluation. The average amount of tofu/tempeh production in a day reaches 10-50 kg in Semanan, as well as the use of soybean raw materials on average ranging from 10-50 kg/day. As much as 53% of the people did not know the potential of tempe/tofu wastewater to be alternative energy for cooking, however, very high enthusiasm was shown by the analysis of the questionnaire with 100% of the people willing to become volunteers as a contribution to procuring waste processing technology that could produce alternative energy sources. This program has been followed up in the form of research on the Faculty's Excellence Research scheme, and this follow-up needs to be integrated.